2013
DOI: 10.1097/der.0b013e31827ede32
|View full text |Cite
|
Sign up to set email alerts
|

EMPACT Syndrome Associated with Phenobarbital

Abstract: Intracranial malignancies can be complicated by seizure activity, and anticonvulsants such as phenytoin are usually administered to prevent this neurological kind of complication. Cranial radiation therapy is instead the treatment of choice when the tumor is unresectable. Anyway, the combination of phenytoin and cranial radiation therapy can lead to a rare and severe mucocutaneous complication called EMPACT syndrome. It is composed of "erythema (E) multiforme (M) associated with phenytoin (P) and (A) cranial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…About thirty cases have been described so far 1, 2, 4. No correlation was found between size and severity of cutaneous eruptions and the dose of phenytoin or radiation therapy, or the origin or size of intracranial malignancy 3, 5. In previous case reports, associated cancers were glioblastoma multiforme, glioma, astrocytoma or tumors with brain metastases like lung cancer, breast cancer, germinoma, melanoma, angiosarcoma, chondrosarcoma or bronchial carcinoma.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…About thirty cases have been described so far 1, 2, 4. No correlation was found between size and severity of cutaneous eruptions and the dose of phenytoin or radiation therapy, or the origin or size of intracranial malignancy 3, 5. In previous case reports, associated cancers were glioblastoma multiforme, glioma, astrocytoma or tumors with brain metastases like lung cancer, breast cancer, germinoma, melanoma, angiosarcoma, chondrosarcoma or bronchial carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Many mechanisms were asserted in the pathway of phenytoin metabolism. Animal studies showed that radiation to brain may cause a rise in cellular autoimmunity by upregulating mRNA expression of immunologic cytokines in rats 5 . Radiation may also induce a defect in epoxide hydrolase, an enzyme that breaks down the drug, causing accumulation of oxidative metabolites 2, 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of EM confi ned to the radiation fi eld during or following cranial radiation in patients receiving prophylactic anticonvulsant therapy with phenytoin was recently defi ned as EMPACT (Erythema Multiforme associated with Phenytoin And Cranial radiation Therapy) [ 21 , 22 ]. Phenobarbital has also been reported to cause EMPACT [ 23 ].…”
Section: Erythema Multiforme-like Drug Eruptionmentioning
confidence: 97%